Researcher Profile: Derek Lawson (Journal of Financial Therapy, 2019)
Derek Lawson, Ph.D., CFP®, is an Assistant Professor of Personal Financial Planning at Kansas State University and a partner and financial planner at Priority Financial Partners, based in Durango, CO. His research is practitioner-focused, allowing him to combine his past and present experience as a financial planner with his research interests
Keywords: financial therapy; research and practice